Callogenesis and plant regeneration of Jasminum sambac L. (Jasmine) - Farzinebrahimi, R.; Rashid, K.; Mat Taha, R.; Ishak, K.A. (2014)
In the present study, regeneration of J sambac var. Maid of Orleans through direct and indirect organogenesis has been investigated. In direct organogenesis, shoot development from young stems (each contained one nodal part) cultured in MS media supplemented with a combination of BAP (3.0 mg L-1) and NAA (I mg L'!) showed 20% shoot regeneration. For indirect organogenesis, among different explants only young stems inoculated in MS media supplemented with 2, 4- D (0.5 mg L-!) yielded callus. In order to identify embryogenic cells in callus, double staining test was carried out, and embryogenic callus was detected in all formed callus, in MS media supplemented with different concentrations of2, 4-D. Further studies on cell suspension culture by using liquid MS media supplemented with various concentrations of 2, 4- D (0.5 mg") has also been done. Different colors of callus were obtained in the present study including green, yellowish and whitish. However, the entire callus did not show any development of organogenesis.